Development and quality assessment of pork sandwich spread incorporated with different levels of antioxidant mixture (BHA and BHT) during frozen storage (−18 ± 1°C). Issue 6 (14th November 2016) - Pandey, Anurag; Keshri, Ramesh Chandra; Kumar, Yogesh
Abstract : Purpose: This paper aims to develop a good quality pork sandwich spread incorporated with different levels of antioxidant mixture [butylated hydroxyanisole (BHA) + butylated hydroxytoluene (BHT); 1:1] and to assess sensory, physico-chemical and microbiological properties of frozen product during storage. Design/methodology/approach: Three levels of antioxidant mixture (BHA + BHT; 1:1) i.e. 100, 200 and 400 ppm were tried, and the product was compared for physico-chemical, microbiological and sensory properties along with the control during frozen storage (−18 ± 1°C). Findings: pH and water activity decreased significantly ( p < 0.05), whereas water holding capacity, 2-thiobarbituric acid reacting substances value, total plate count and psychrotrophic count increased significantly ( p < 0.05) during storage period. No coliform, yeast and molds were detected throughout the study period. There was non-significant ( p < 0.05) effect of antioxidant treatment on the scores of colour, texture, juiciness, adhesion ability and spreadability, but scores for flavour and overall acceptability significantly ( p < 0.05) increased. Research limitations/implications: Pork sandwich spread is envisaged to help in providing nutrition to a large section of needy population and will add a new dimension to the convenience foods. Originality/value: Antioxidant mixture (BHA + BHT, 1:1) treatment improved the sensory and microbiological properties of pork sandwich spread at frozen storage (−18 ± 1°C). At the end of storage period (60 days), the pork sandwich spread was found safe for human consumption. Hence, BHA and BHT antioxidant mixture could be used to improve quality attributes of meat products during storage.